Business models for internet of things providers in South Africa - Mogase, Duduetsang Kgosi (My University, 2019)
Purpose: To investigate existing IoT business models and use cases across South African and global companies; with the extended primary aim of exploring vertical taper integration across the IoT value chain as a candidate future IoT business model, for IoT providers aiming to exploit future IoT opportunities, and be in a position to control and deliver business outcomes based value across the IoT value chain, from edge-to-application. Design: Field data was gathered through interviews with IoT industry practitioners. Inductive data analysis and interpretation was used to analyse the raw qualitative data collected through structured interviews, transcribed audio recordings and documentation provided by the research participants - IoT industry practitioners. Findings: Vertical Taper Integration, as a value based business model is indeed, the ideal candidate future IoT business model for edge-to-application IoT providers who wish to exploit future IoT opportunities and be in a position to control and deliver business outcomes-based value across the IoT value chain, from edge-to-application. However, IoT providers operating from the commoditised lower end of the IoT stack, operating in specific verticals of the stack (e.g. sensors and actuators), are still profitable with their transaction based business model and are comfortable operating from this part of the stack for the time being, until such a time that their skills, capabilities, scalability and capital allow them to move further up the IoT stack and too, become an end to end edge-to-application IoT provider. Research limitations: The scope of companies covered in the research was limited due to the confidentiality concerns raised by candidate research participants, as a result of the researcher working for a competing company. However, a breadth of industry verticals was covered from the research participants interviewed, given their experience across multiple industry verticals in South Africa and globally. Value: For those IoT providers aspiring to or focused on controlling and delivering across the entire IoT value chain (also referred to as the IoT stack), from edge-to-application, vertical taper integration into each layer of the IoT value chain will enable that, unlike current standalone IoT business models. Vertical Taper Integration will provide the IoT provider with an inimitable competitive advantage in comparison to current IoT providers, as well as a future IoT Business Model capable of fully exploiting emerging IoT opportunities from billions of connected devices projected for and beyond 2020.
MBA
Keywords: IoT; IoT Business Model; IoT Value Chain; Business-outcomes; IoT Stack; Vertical Taper Integration; Go-to-Market